Aurora Luque (ed. y trad.), Safo. Poemas y testimonios, Barcelona, El Acantilado, 2004, 190 pp. (Minerva, 2019)
Review: Aurora Luque (ed. y trad.), Safo. Poemas y testimonios, Barcelona, El Acantilado, 2004, 190 pp.